The Effect of Islamic Capital Market Instruments on Indonesia's Economic Growth is Moderated by The Money Supply - Robiatul Adewiyah; Anton Bawono (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This article examines the relationship between Islamic capital market instruments and Indonesia's economic growth, taking into account the moderating role of the money supply. With the rise of Islamic finance and the increasing significance of the Islamic capital market, understanding the dynamics between these instruments and economic growth becomes crucial. The method used in this research is quantitative research which focused on the national economic growth in Indonesia from the year 2011 to 2021. The data were used from the economic growth, Sharia stock index, sukuk, Sharia mutual funds, and total money supply in Indonesia from the period of research which is the quarterly data. The results of this study are that the Islamic stock index has a positive effect on economic growth. Sukuk has a positive effect on economic growth. On the other hand, sharia mutual funds do not affect economic growth. The money supply is not able to moderate the effect of the Sukuk on economic growth.